2019
DOI: 10.3390/cancers11101456
|View full text |Cite
|
Sign up to set email alerts
|

N6-Isopentenyladenosine Inhibits Colorectal Cancer and Improves Sensitivity to 5-Fluorouracil Targeting FBXW7 Tumor Suppressor

Abstract: N6-isopentenyladenosine has been shown to exert potent in vitro antitumor activity on different human cancers, including colorectal cancer. Although some potential biochemical targets have been identified, its precise mechanism of action remains unclear. We found that N6-isopentenyladenosine affects colorectal cancer proliferation in in vitro models carrying different mutational status of FBXW7 and TP53 genes, and in HCT116 xenografts in SCID mice, by increasing the expression of the well-established tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
2
8
0
1
Order By: Relevance
“…However, the multitude of their effects described in numerous studies ( Laezza et al, 2009 ; Ottria et al, 2010 ; Ciaglia et al, 2014 ; Ciaglia et al, 2017a ; Ciaglia et al, 2017b ; Dassano et al, 2014 ; Pisanti et al, 2014 ; Ciaglia et al, 2018 ; Ranieri et al, 2018 ), and the chemical nature of these molecules, suggests that a precise mechanism explaining their pleiotropic effects in different tumor-related mechanisms, ranging from the tumor microenvironment to immunomodulation, has not yet been fully identified. Recently, we reported that IPA inhibits colorectal cancer (CRC) proliferation in vitro and in vivo by increasing the expression of the tumor suppressor FBXW7 and, in turn, regulating the FBXW7/SREBP/FDPS axis, corroborating with previous studies ( Fiore et al, 2019 ). FBXW7 is a component of the SCF-E3 ubiquitin ligase complex responsible for the degradation of various oncoproteins and transcription factors, such as p100/NFκB, HIF-1α, c-Myc, SREBP, and Mcl1 ( Sailo et al, 2019 ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the multitude of their effects described in numerous studies ( Laezza et al, 2009 ; Ottria et al, 2010 ; Ciaglia et al, 2014 ; Ciaglia et al, 2017a ; Ciaglia et al, 2017b ; Dassano et al, 2014 ; Pisanti et al, 2014 ; Ciaglia et al, 2018 ; Ranieri et al, 2018 ), and the chemical nature of these molecules, suggests that a precise mechanism explaining their pleiotropic effects in different tumor-related mechanisms, ranging from the tumor microenvironment to immunomodulation, has not yet been fully identified. Recently, we reported that IPA inhibits colorectal cancer (CRC) proliferation in vitro and in vivo by increasing the expression of the tumor suppressor FBXW7 and, in turn, regulating the FBXW7/SREBP/FDPS axis, corroborating with previous studies ( Fiore et al, 2019 ). FBXW7 is a component of the SCF-E3 ubiquitin ligase complex responsible for the degradation of various oncoproteins and transcription factors, such as p100/NFκB, HIF-1α, c-Myc, SREBP, and Mcl1 ( Sailo et al, 2019 ).…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, in vitro FBXW7 overexpression significantly suppressed proliferation, invasion, and migration and, most importantly, was found to increase temozolomide (TMZ) toxicity in a resistant clone ( Lin et al, 2018 ). We previously found that, in FBXW7 - and TP53 -wild-type CRC cells, IPA-mediated restoration of FBXW7 tumor suppressor translates into synergism with 5-fluorouracil ( Fiore et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many mechanisms of tumor chemoresistance have been discovered and elucidated, it remains the leading cause of chemotherapy failure, especially in relapsed or metastatic tumors. Re-sensitizing cancer cells to the drugs by using novel effective strategies is a promising approach to overcome the chemoresistance and improve clinical treatment [ 38 , 39 ]. Recently, we evaluated uL3 clinical significance in colon cancer and demonstrated that uL3 expression in colon tumor tissues is downregulated; in particular, the decrease in uL3 mRNA levels associated with malignance progression and tumor grade and were inversely proportional to the ratio Bcl-2/Bax [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation or deletion of these E3 ligase genes induces carcinogenesis by attenuating c-Myc degradation. Anticancer drugs, including lanatoside C, diminish cancer cell growth by upregulating ubiquitination and degradation of c-Myc in cancer [161][162][163]. Ubiquitination of c-Myc can also be regulated by interaction with other molecules.…”
Section: Ubiquitination Of C-mycmentioning
confidence: 99%